SOCIAL STRATIFICATION IN GUNTURU VILLAGE, HERLANG DISTRICT, BULUKUMBA REGENCY - Tauzi, Azlan; Falihin, Dalilul (Universitas Negeri Makassar, 2022)
This study aims to: 1) Find out the description of social stratification in Gunturu Village, Herlang District, Bulukumba Regency. 2) Knowing the form of social interaction between the karaeng group and the ata group in Gunturu Village, Herlang District, Bulukumba Regency. The type of research used by the researcher is descriptive qualitative. The data collection techniques through, documentation, observation, and interviews. The data collection process carried out by the researchers included: data collection, data reduction, data presentation and conclusion drawing. The results showed 1) The description of social stratification in Gunturu Village, Herlang District, Bulukumba Regency had several indicators, namely wealth, power, honor, and knowledge. . Wealth is categorized as